Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1614/wt-d-15-00057.1
|View full text |Cite
|
Sign up to set email alerts
|

Control of Johnsongrass in the Absence of Glyphosate in Midsouth Cotton Production Systems

Abstract: Johnsongrass populations that are resistant to 5-enolpyruvyl-3-shikimate synthase (EPSPS)–, acetyl coenzyme A carboxylase (ACCase)–, or acetolactate synthase (ALS)–inhibiting herbicides are increasingly common throughout the midsouth. Three trials were conducted in 2012, 2013, and 2014 in Fayetteville, AR and Alexandria, LA to evaluate strategies with and without ALS- and ACCase inhibitors for management of rhizomatous johnsongrass in the absence of glyphosate. Fluometuron or fluometuron plus pyrithiobac appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…There was Johnsongrass regrowth from every herbicide application except from glyphosate (Figure 3). Therefore, all herbicide applications controlled only the above ground Johnsongrass biomass (shoot) and failed to control below ground As reported by Meyer et al (2015) effective management of severe infestations or escapes of 15-cm tall Johnsongrass was achieved by various herbicide combinations consisting mainly of glufosinate plus clethodim, as it has been observed in this study (Figure 4).…”
Section: Johnsongrass Controlsupporting
confidence: 70%
“…There was Johnsongrass regrowth from every herbicide application except from glyphosate (Figure 3). Therefore, all herbicide applications controlled only the above ground Johnsongrass biomass (shoot) and failed to control below ground As reported by Meyer et al (2015) effective management of severe infestations or escapes of 15-cm tall Johnsongrass was achieved by various herbicide combinations consisting mainly of glufosinate plus clethodim, as it has been observed in this study (Figure 4).…”
Section: Johnsongrass Controlsupporting
confidence: 70%
“…Johnsongrass is a perennial species that has historically been a highly problematic weed in row-crop production [28,29]. In the absence of glyphosate, Johnson et al [30] concluded that a single application of glufosinate alone is not sufficient to control Johnsongrass, and sequential applications of glufosinate plus clethodim were generally needed for acceptable control [31,32]. Weed spectrum and weather conditions may play a role in the recommendations of specific herbicide programs, and everything should be carried out to maximize the utility of the herbicides (i.e., glufosinate) utilized in those programs to achieve maximum weed control and mitigate the likelihood of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The trials were initiated in fields that did not have a native population of johnsongrass, and the johnsongrass evaluated was easily identified as plants sown into rows using a planter. Single applications of glufosinate at ≥595 g ha -1 or clethodim at ≥136 g ha -1 provided >90% control of seedling johnsongrass in both experiments, whereas both Johnson et al (2014b) and Meyer et al (2015b) reported that two applications of glufosinate were needed to control rhizomatous johnsongrass.…”
Section: Weed Technologymentioning
confidence: 88%
“…Glufosinate will control a broad spectrum of grass and broadleaf weeds, and the utilization of various technologies with glufosinate-resistant traits will probably increase the use of glufosinate POST in the coming years. As a single application of glufosinate is not always enough to control emerged grasses (Culpepper et al 2000;Meyer et al 2015b), a detailed investigation on the performance of glufosinate in mixtures on common, hard-to-control grass weeds in the Midsouth United States is needed. Four common and troublesome grass weeds in this region are barnyardgrass, broadleaf signalgrass, large crabgrass, and johnsongrass (Webster 2012(Webster , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation